The Role of the School Principle in Improving the Quality of Education - Munzilin, Munzilin; Fitrah, Hariki; Rahmi Novalita, Rahmi Novalita (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to explore the role of school principals in improving the quality of education at the 16 Juli Public Elementary School, Bireuen District. This type of research is descriptive using a qualitative approach. The research informants were school principals and teachers at the Juli 16 Public Elementary School. The informant collection technique used the snowball sampling technique. The data collection tool uses field notes. Data collection techniques consist of observation, interviews, and documentation. Data analysis using data reduction, data display, and drawing conclusions. The results showed that the role of the principal in improving the quality of education at the Juli 16 Public Elementary School consisted of; a) the role of the principal as an educator, namely providing training and guidance to teachers in improving teacher performance, b) the role of the principal as a manager, namely establishing planning, implementing, organizing, and implementing school program activities, c) the role of the principal as an administrator, namely the ability to manage school administration, finance, student affairs, school facilities and infrastructure, d) the role of the principal as supervisor, namely, the ability to compile and implement supervision programs involving deputy principals and teachers.